2002
DOI: 10.1034/j.1601-5215.2002.140302.x
|View full text |Cite
|
Sign up to set email alerts
|

Low IQ scores in schizophrenia: primary or secondary deficit?

Abstract: These findings are important in considering the value of intelligence levels in schizophrenia. IQ scores should be judged in combination with cognitive functioning and school career to assess a patients capabilities in society. Cognitive functions and other variables might have a considerable influence on IQ scores. This rises the question of whether the low IQ scores are a primary or secondary deficit. Schizophrenia patients may have normal IQs, but could be less capable of making an IQ-test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…This slowing may have important implications for understanding the sources of dysfunction in schizophrenia (cf. Mohamed et al, 1999;Van Beilen et al, 2002). In addition to this psychomotor slowing, there was evidence for more specific problems with planning, particularly when the task requirements were incompatible with a normal preference.…”
Section: Discussionmentioning
confidence: 99%
“…This slowing may have important implications for understanding the sources of dysfunction in schizophrenia (cf. Mohamed et al, 1999;Van Beilen et al, 2002). In addition to this psychomotor slowing, there was evidence for more specific problems with planning, particularly when the task requirements were incompatible with a normal preference.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported improvement in specific subtests, global cognitive change inlarge comparative studies in the first episode and chronic schizophrenia rarely reach an effect size of more than 0.3. [6] Based on the above study the authors feel interested to see the relationship between intelligence to cognitive function in schizophrenia patients.…”
Section: Introductionmentioning
confidence: 99%